2021
DOI: 10.1038/s41435-021-00157-1
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in Toll-like receptor 7 results in functional impairment and downregulation of cytokine-mediated signaling in COVID-19 patients

Abstract: Toll-like receptors (TLR) are crucial components in the initiation of innate immune responses to a variety of pathogens, triggering the production of pro-inflammatory cytokines and type I and II interferons, which are responsible for innate antiviral responses. Among the different TLRs, TLR7 recognizes several single-stranded RNA viruses including SARS-CoV-2. We and others identified rare loss-of-function variants in X-chromosomal TLR7 in young men with severe COVID-19 and with no prior history of major chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…Results from the severe COVID-19 outcome analyses of TLR7 with other masks also nearly reach our statistical significance threshold, with larger effects found in the pLoF mask (OR: 13.6, 95% CI: 4.41-44.3, p=1.64×10 -5 ) and smaller effect in the coding1 mask (OR: 3.12, 95% CI: 1.91-5.10, p=5.30×10 -6 ), though the latter was balanced by smaller standard errors due to the larger number of cases (3275 cases in coding1 vs 1577 in pLoF), as expected. These findings further support previous reports of TLR7 errors of immunity underlying severe COVID-19 presentations 17,2730 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Results from the severe COVID-19 outcome analyses of TLR7 with other masks also nearly reach our statistical significance threshold, with larger effects found in the pLoF mask (OR: 13.6, 95% CI: 4.41-44.3, p=1.64×10 -5 ) and smaller effect in the coding1 mask (OR: 3.12, 95% CI: 1.91-5.10, p=5.30×10 -6 ), though the latter was balanced by smaller standard errors due to the larger number of cases (3275 cases in coding1 vs 1577 in pLoF), as expected. These findings further support previous reports of TLR7 errors of immunity underlying severe COVID-19 presentations 17,2730 .…”
Section: Resultssupporting
confidence: 92%
“…Other methods may be needed in future analysis to soften this assumption, though some of these cannot be easily meta-analyzed across multiple cohorts directly from summary statistics (e.g., SKAT-O 41 ). Similarly, methods that combine both rare and common variants might also provide additional insights into disease outcomes 30,42 . Second, our results highlight the importance at looking at different categories of variants through different masks to increase sensitivity and specificity of our burden tests.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired signal pathways of TLR7 were associated with the changes of mRNA CXCL10. It was reported that the CXCL10 mRNA was significantly decreased in two rare variants of TLR7: 920Lys and Asp41Glu in patients with SARS-CoV-2 infection in comparison to healthy donors [ 61 ]. The Described study is in accordance with previous findings focusing on the role of TLR7 and CXCL10, which is directly associated with TLR7 in severe course of COVID-19 [ 59 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding has been replicated by Fallerini et al 7 in 561 individuals and Asano et al 5 in a larger sample of 1,533 individuals. Both studies and a further follow-up study by Mantovani et al 43 performed functional investigations highlighting the role of TLR7 loss of function in impaired type I interferon responses.…”
Section: Genetic Findingsmentioning
confidence: 99%